KARAKTERISTIK ISOLAT Rhizoctonia sp. PATOGENIK DAN Rhizoctonia MIKORIZA PADA TANAMAN ANGGREK TANAH (Spathoglottis plicata) - S. Soelistijono; Christanti Sumardiyono; Achmadi Priyatmojo; Endang Semiarti (JURNAL ILMIAH AGRINECA, 2012)
Mycorrhizal Rhizoctonia is a fungus that capable to associate with terrestrial orchids. Apart from being mycorrhizal, there are isolates of Rhizoctonia sp. that are pathogenic and caused root rot disease on Spathoglottis plicata. This study aimed to know the differences between pathogenic Rhizoctonia sp. and mycorrhizal Rhizoctonia in morphology and molecular structure using RAPD technique. The results showed that colony colour, Â cell lenght and nucleus number a several isolates of pathogenic Rhizoctonia sp. and of mycorrhizal Rhizoctonia on S. plicata had no differences, but had differences on cell thickness and isolate grouping based on hyphal anastomosis test. RAPD molecular technique showed that each isolate of pathogenic Rhizoctonia sp. and mycorrhizal Rhizoctonia had differences on DNA structure.